Role of Sheikh Wan Ahmad Al-Fatani in the Malay publications and printing in the Middle East - Ermy Azziaty Rozali (Universiti Kebangsaan Malaysia, 2014)
The Middle East has become the focus of attention for the Malays to gain education. However, in the addition to education, the expansion of publication and printing in Malay script do play substantial role in the development of intellectual and knowledge. Renowned scholar, Sheikh Wan Ahmad al-Fatani is known through the printing of various works of Islamic knowledge into Malay script. It is said that he gained the capital, support and credence from the Ottoman Empire. Under the reign of Sultan Abdul Hamid II (1876-1909) he was appointed as the supervisor of Matbaah al-Mirriyyah al-Kainah in Mecca. Financing from the Ottoman Empire helps the Malay script works to be printed on a large scale and disseminated throughout the Muslim world. Therefore, this paper is designed to unveil the role of Sheikh Wan Ahmad in the expansion of publication and printing in Malay script in the Middle East that produces significant contributions in the Malay World epistemology image formation within the Middle East region.